Adobe Illustrator - Fridsma, Lisa (Visual quickstart guide., 2022)
Visual QuickStart Guide is an easy, visual approach to learning. Concise steps and explanations guide you through Adobe Illustrator, getting you up and running in no time. In addition, the free Web Edition of the book includes more than 40 videos, enhancing and expanding the information in the book while providing an alternative method for learning. Whether youre an experienced designer or an enthusiastic newcomer, Illustrator gives you all the tools you need to begin creating impressive vector artwork. Learn how to navigate the application and set up your documents to start drawing quickly, using a variety of tools and features. Then youll move on to applying appearance attributes and effects for adding visual interest to your artwork. Once your artwork is complete youll learn how to save and export it using best practices.